INNOVATIVE PRACTICES OF UNIVERSITY PROFESSORS: A SURVEY-BASED STUDY IN HIGHER EDUCATION MANAGEMENT - I. A. Imomov; F. B. Egamberdiev (Sciental Journals Publishing, 2025)
This study explores the innovation activity of university professors within the domain of education management. Using a structured questionnaire distributed to a simulated sample of 50 faculty members across various disciplines, the research assesses engagement with innovative teaching methods, digital tools, collaboration practices, and institutional support for innovation. Results indicate a generally positive trend toward innovation, with notable variations based on academic rank and administrative roles. The findings offer practical recommendations for policy-makers and institutional leaders to foster innovation-oriented environments in higher education.
Keywords: Innovation activity, university professor, higher education management, teaching innovation, digital pedagogy, academic leadership